Penerapan Metode Fuzzy Tsukamoto dalam Penilaian Kinerja Karyawan di Perusahaan Air Minum Kabupaten OKU - Joko Kuswanto; Benny Maulana; Ryan Vernando; Suhendra Berta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One effective way to encourage employee motivation is to provide recognition in the form of rewards that are in accordance with their performance. The assessment process to determine the best employees needs consideration and is certainly not easy because it must be in accordance with the criteria set by the company. Seeing these conditions, the need for the application of computerized systems that can be a solution to overcome complexity in decision making. One method in decision support systems is the fuzzy method. The method used in this study is Tsukamoto's fuzzy method. The employee appraisal process is carried out based on several criteria such as performance, discipline, and ability. From the calculation results, a Z value of 57.5 was obtained. The value is included in the category considered for reward. Based on the results of the assessment, it can be concluded that Tsukamoto's fuzzy method can be applied in employee performance appraisal.